The carotid rete and artiodactyl success - Mitchell, G (The Royal Society, 2008)
Since the Eocene, the diversity of artiodactyls has increased while that of perissodactyls has decreased. Reasons given for this contrasting pattern are that the evolution of a ruminant digestive tract and improved locomotion in artiodactyls were adaptively advantageous in the highly seasonal post-Eocene climate. We suggest that evolution of a carotid rete, a structure highly developed in artiodactyls but absent in perissodactyls, was at least as important. The rete confers an ability to regulate brain temperature independently of body temperature. The net effect is that in hot ambient conditions artiodactyls are able to conserve energy and water, and in cold ambient conditions they are able to conserve body temperature. In perissodactyls, brain and body temperature change in parallel and thermoregulation requires abundant food and water to warm/cool the body. Consequently, perissodactyls occupy habitats of low seasonality and rich in food and water, such as tropical forests. Conversely, the increased thermoregulatory flexibility of artiodactyls has facilitated invasion of new adaptive zones ranging from the Arctic Circle to deserts and tropical savannahs.